Raw materials of near-zero shrinkage silicon-based ceramic core and preparation method of near-zero shrinkage silicon-based ceramic core

By introducing metal zirconium powder into the ceramic core raw materials, using in-situ oxidation expansion and phase change effects, near-zero shrinkage and bending strength improvement are achieved, and the problem of insufficient dimensional accuracy and stability of the ceramic core is solved, and is suitable for complex shapes Design and development of ceramic cores.

CN119320268AActive Publication Date: 2025-01-17SHANGHAI UNIV

Patent Information

Application Number
CN202411874398.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-17
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing ceramic cores lack dimensional accuracy and stability in complex inner cavity structures, resulting in unqualified casting of turbine blades. The existing regulators have limited effects in improving dimensional accuracy and affect removal.

Method used

The near-zero shrinkage silicon-based ceramic core raw materials, including refractory material powder, zirconium silicate powder and metal zirconium powder, can achieve near-zero shrinkage of ceramic core through the in-situ oxidation expansion and phase change effect of metal zirconium powder, and improve the near-zero shrinkage of ceramic core. Its room temperature and high temperature bending strength.

Benefits of technology

It significantly improves the dimensional accuracy and stability of the ceramic core, reduces the sintering shrinkage rate, and enhances the bending strength. It is suitable for the design and development of complex-shaped ceramic cores.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a raw material of a near-zero shrinkage silicon-based ceramic core and a preparation method thereof, the raw material of the ceramic core comprises refractory material powder, zirconium silicate powder and metal zirconium powder, and the refractory material powder, the zirconium silicate powder and the metal zirconium powder are mixed according to the proportion to form the raw material of the ceramic core; ceramic core raw materials are added into liquid paraffin to form ceramic core slurry, the ceramic core slurry is used for obtaining a ceramic core biscuit through a hot-pressing injection molding method, and the ceramic core biscuit is subjected to powder burying sintering to obtain the ceramic core. Volume shrinkage generated in the sintering process of the ceramic core is made up through in-situ synthesis oxidation expansion of the metal zirconium powder, meanwhile, shrinkage of the ceramic core can be made up through generated zirconium dioxide due to the phase change effect, near-zero shrinkage of the silicon-based ceramic core in the sintering process is achieved under the dual effects of in-situ oxidation and the phase change effect, and the silicon-based ceramic core has the good sintering performance. Meanwhile, the generated zirconium dioxide improves the room-temperature bending strength and the high-temperature bending strength of the ceramic core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic core preparation, and in particular to a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof. Background Art

[0002] As a key hot end component of an aero-engine, the temperature bearing capacity of an aero-engine turbine blade plays an important role in improving the overall performance of the aero-engine. At present, the temperature bearing capacity can only be further improved by improving the alloy material. The design of the hollow air-cooled structure of the blade has become the main means to improve the temperature bearing capacity of the blade, and the design and preparation of the complex ceramic core is the key to realizing the hollow air-cooled structure of the blade. With the continuous improvement of air cooling efficiency, the inner cavity structure of the blade is becoming more and more complex, and the size of some channels is getting smaller and smaller, which requires the ceramic core to have precise and fine dimensions, such as double-walled ceramic cores. These complex structures have higher requirements on the performance of the ceramic core, and at the same time, the dimensional accuracy of the ceramic core is also higher, that is, the ceramic core needs to have high dimensional accuracy.

[0003] At present, the method actually used to manufacture ceramic cores with complex shapes is investment casting. However, when ceramic cores prepared by this technology encounter complex inner cavity structures, due to the poor dimensional accuracy of the core, the local fine structure often deforms or breaks, causing the blade casting to be unqualified. At the same time, the dimensional stability of the ceramic core is poor, and it is very easy to cause the core to mismatch during the high-temperature pouring stage due to the large high-temperature deflection, resulting in unqualified casting blades. Therefore, in order to improve the dimensional accuracy of the inner cavity of the turbine blade and improve the casting yield, it is of great significance to develop a ceramic core with high dimensional accuracy and stability.

[0004] Domestic and foreign researchers have also carried out a lot of work to improve the dimensional accuracy and stability of ceramic cores, such as introducing inert mineralizers to inhibit the shrinkage of ceramic cores during sintering.

[0005] The existing patent CN115894051A discloses a sintering shrinkage regulator for silicon-based ceramic cores and a preparation method thereof, wherein the sintering shrinkage regulator for silicon-based ceramic cores comprises: 10-30 parts of kyanite powder, 20-45 parts of cristobalite powder, 10-40 parts of mullite powder, 10-20 parts of activated alumina powder, 0-10 parts of elemental silicon powder, 0-10 parts of silicon carbide powder and 0-10 parts of silicon nitride powder. The method can add the regulator without changing the performance of the ceramic core, and freely adjust the sintering size of the ceramic core, thereby avoiding sacrificing the performance of the ceramic core in order to ensure sintering shrinkage.

[0006] Existing patent CN115108818A discloses a low-shrinkage and low-flexure silicon-based ceramic core raw material and a preparation method, including refractory powder and a mineralizer, wherein the mineralizer is a composite mineralizer, and the composite mineralizer includes zirconium silicate and aluminum silicate, wherein the weight percentage of the aluminum silicate in the ceramic core raw material is 1-15%, and the weight percentage of the zirconium silicate in the ceramic core raw material is 5-10%. The present invention can be used to prepare a silicon-based ceramic core with low sintering shrinkage and low high-temperature deformation, thereby improving the sintering success rate of the ceramic core. Existing research results show that by adding such mineralizers, the dimensional accuracy of the ceramic core can be effectively improved, thereby realizing the manufacture of hollow blades with high dimensional accuracy. However, such methods are still limited in terms of improving the dimensional accuracy of the ceramic core, and also introduce a large amount of inert oxide or non-oxide raw materials, affecting the removal of the ceramic core.

[0007] In summary, the above two existing patents have not completely solved the problem of improving the dimensional accuracy and stability of ceramic cores in the prior art. Summary of the invention

[0008] Based on the above technical problems, the present invention proposes a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof, which solves the problem in the prior art that the dimensional accuracy and stability of the ceramic core need to be further improved.

[0009] To achieve the above purpose, the present invention proposes a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof. The specific technical solution is as follows:

[0010] A raw material for a near-zero shrinkage silicon-based ceramic core comprises refractory powder, zirconium silicate powder and metal zirconium powder, wherein the weight percentage of the refractory powder in the raw material is 70-89%, the weight percentage of the zirconium silicate powder in the raw material is 10-20%, and the weight percentage of the metal zirconium powder in the raw material is 1-10%.

[0011] Furthermore, the weight percentage of the refractory powder in the raw material is 80-89%, the weight percentage of the zirconium silicate powder in the raw material is 10-15%, and the weight percentage of the metal zirconium powder in the raw material is 1-5%.

[0012] Furthermore, the weight percentage of the refractory powder in the raw material is 85-88%, the weight percentage of the zirconium silicate powder in the raw material is 10.5-12%, and the weight percentage of the metal zirconium powder in the raw material is 1.5-3%.

[0013] Furthermore, the particle size range of the refractory powder is 1-60 μm and the powder purity is not less than 99.95%, the particle size range of the zirconium silicate powder is 1-50 μm and the powder purity is not less than 98.99%, and the particle size range of the metal zirconium powder is 1-10 μm and the powder purity is not less than 99.99%.

[0014] Furthermore, the refractory material powder is quartz glass powder.

[0015] The present invention also provides a method for preparing a near-zero shrinkage silicon-based ceramic core, using the raw materials of the near-zero shrinkage silicon-based ceramic core to prepare a ceramic core, and the preparation method specifically comprises:

[0016] S1. Mixing the ceramic core raw materials to form a ceramic core slurry;

[0017] S2. Using a ceramic core slurry to form a ceramic core blank;

[0018] S3. The ceramic core blank is buried with powder and sintered to obtain a ceramic core.

[0019] Furthermore, in step S1, the ceramic core raw material is added to the dispersant in batches, and vacuum-stirred until uniform to obtain a ceramic core slurry.

[0020] Furthermore, in step S1, the ceramic core raw material is added to the melted paraffin in batches, and vacuumed and stirred until uniform to obtain a ceramic core slurry;

[0021] The melting temperature of the paraffin wax is 80-95°C.

[0022] Further, in step S2, the ceramic core slurry is added into a core pressing machine, and a ceramic core blank is obtained by a hot pressing injection molding method;

[0023] The molding pressure of the core pressing machine is 5-10MPa.

[0024] Furthermore, in step S3, the final sintering temperature is 1100-1300° C., and the holding time is 4-15 hours;

[0025] The sintering heating process includes multiple stages, the heating range of each stage is 150-300°C, the heating rate of each stage is 2-8°C / min, and the insulation time after heating in each stage is 4-15h;

[0026] The multiple stages include: the first stage: room temperature to 200°C, the heating rate is 2°C / min, and the temperature is kept at 200°C for 4 hours; the second stage: 200°C to 400°C, the heating rate is 2°C / min, and the temperature is kept at 400°C for 5 hours; the third stage: 400°C to 650°C, the heating rate is 3°C / min, and the temperature is kept at 650°C for 8 hours; the fourth stage: 650°C to 950°C, the heating rate is 5°C / min, and the temperature is kept at 950°C for 10 hours; the fifth stage: 950°C to a maximum of 1250°C, the heating rate is 8°C / min, and the temperature is kept for 12 hours.

[0027] Based on the above technical solution, the present invention has at least the following beneficial effects:

[0028] 1. The present invention proposes a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof. The volume shrinkage of the ceramic core during the sintering process is compensated by the in-situ spontaneous oxidation expansion of metal zirconium powder. At the same time, the generated zirconium dioxide will compensate for the shrinkage of the ceramic core due to the phase change effect. Under the dual effects of in-situ oxidation and phase change effects, the near-zero shrinkage of the ceramic core during the sintering process is achieved, thereby improving its dimensional accuracy.

[0029] 2. The present invention proposes a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof, and the zirconium dioxide generated by metal zirconium powder improves the room temperature flexural strength and high temperature flexural strength of the silicon-based ceramic core.

[0030] 3. The present invention proposes a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof, and specifically designs the component content of the metal zirconium powder in the ceramic core raw material, so that the ceramic core raw material can achieve excellent technical effects.

[0031] 4. The present invention proposes a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof, which is also applicable to the design and development of ceramic cores of other systems and has important promotion value. DETAILED DESCRIPTION

[0032] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0033] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0034] In order to solve the problem in the prior art that the dimensional accuracy and stability of ceramic cores need to be improved, the present invention provides a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof.

[0035] To achieve the above-mentioned purpose, the present invention proposes a raw material for a near-zero shrinkage silicon-based ceramic core and a preparation method thereof. On the basis of refractory powder and mineralizer, metal zirconium powder is introduced. During the high-temperature sintering process, the shrinkage of the ceramic core is compensated by the in-situ oxidation expansion of the metal zirconium powder. At the same time, the generated zirconium dioxide will also compensate for the shrinkage of the ceramic core due to the phase change effect. Under the dual effects of in-situ oxidation and phase change effects, the near-zero shrinkage of the silicon-based ceramic core during the sintering process is achieved, and its dimensional accuracy is improved. At the same time, the generated zirconium dioxide will improve the room temperature and high-temperature bending strength of the ceramic core.

[0036] The present invention provides a raw material for a near-zero shrinkage silicon-based ceramic core, comprising refractory powder, a mineralizer and metal zirconium powder, wherein the weight percentage of the refractory powder in the ceramic core raw material is 70%-89%, the mineralizer is zirconium silicate powder, the weight percentage of the zirconium silicate powder in the ceramic core raw material is 10-20%, and the weight percentage of the metal zirconium powder in the ceramic core raw material is 1-10%.

[0037] Among them, refractory powder is made of quartz glass powder, and the chemical composition of zirconium silicate powder includes 64-67% ZrO2 and 33-36% SiO2. The powder particle size range of refractory powder is 1-60μm, and the powder purity is ≥99.95%, the powder particle size range of zirconium silicate powder is 1-50μm, and the powder purity is ≥98.99%, and the powder particle size range of metal zirconium powder is 1-10μm, and the powder purity is ≥99.99%.

[0038] The present invention also proposes a method for preparing a near-zero shrinkage silicon-based ceramic core, which uses the above ceramic core raw material to prepare the ceramic core, specifically comprising:

[0039] S1, mixing ceramic core raw materials to form ceramic core slurry;

[0040] Specifically, refractory powder, zirconium silicate powder and metal zirconium powder are weighed in proportion, and the refractory powder and zirconium silicate powder are placed in a vacuum dryer for drying; the refractory powder, zirconium silicate powder and metal zirconium powder are then mixed evenly to obtain a ceramic core raw material; the ceramic core raw material is added into paraffin melted into liquid, and the powder and the paraffin are evenly mixed through vacuum stirring to form a ceramic core slurry.

[0041] The drying temperature of the vacuum dryer is 95-120°C, and the drying time is 10-24h. The weight percentage of paraffin wax in the ceramic core slurry is 10-20%, and the melting temperature of paraffin wax is 80-95°C.

[0042] S2, forming a ceramic core blank using the ceramic core slurry;

[0043] Specifically, the obtained ceramic core slurry is added into a core pressing machine, and a ceramic core blank is obtained by a hot pressing injection molding method.

[0044] Among them, the molding pressure of the core pressing machine is 5-10MPa.

[0045] S3, burying the ceramic core blank with powder and sintering to obtain a ceramic core.

[0046] Specifically, the ceramic core blank is buried in the air atmosphere and sintered at high temperature to obtain the ceramic core. The final firing temperature is 1100-1300°C, and the sintering temperature rise process includes multiple stages, the temperature rise range of each stage is 150-300°C, the temperature rise rate of each stage is 2-8°C / min, and the holding time after each stage of temperature rise is 4-15h.

[0047] The preparation method of the above-mentioned near-zero shrinkage silicon-based ceramic core is described below through specific data values.

[0048] Example 1

[0049] S1. Prepare 10 kg of ceramic core raw material, weigh quartz glass powder with an average particle size of 20 μm and a purity of 99.95%, zirconium silicate powder with an average particle size of 30 μm and a purity of 98.99%, and metal zirconium powder with an average particle size of 5 μm and a purity of 99.99% according to weight percentages of 89%, 10% and 1% respectively; place the quartz glass powder and zirconium silicate powder in a vacuum dryer and dry them for 12 hours at a temperature of 120° C., and fully and evenly mix the dried quartz glass powder and zirconium silicate powder with the metal zirconium powder to obtain a ceramic core raw material;

[0050] Weigh paraffin wax according to 20% of the weight of the ceramic core slurry and put it into a vacuum mixer for melting. Add the evenly mixed ceramic core raw materials into the melted paraffin wax in batches. The temperature of the paraffin wax is 90° C. Vacuum and stir until uniform to obtain ceramic core slurry.

[0051] S2, transferring the ceramic core slurry to the barrel of the core pressing machine, using a mold to press the green blank, the molding pressure of the core pressing machine is 5MPa, and obtaining the ceramic core green blank;

[0052] S3. Put the ceramic core blank into a sagger, fill it with fillers and then sinter it. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 2℃ / min, and it is kept at 200℃ for 5 hours; the second stage is from 200℃ to 400℃, the heating rate is 2℃ / min, and it is kept at 400℃ for 5 hours; the third stage is from 400℃ to 700℃, the heating rate is 3℃ / min, and it is kept at 700℃ for 8 hours; the fourth stage is from 700℃ to 1000℃, the heating rate is 5℃ / min, and it is kept at 1000℃ for 10 hours; the fifth stage is from 1000℃ to a maximum of 1300℃, the heating rate is 8℃ / min, and it is kept at 12 hours; finally, the ceramic core is obtained after cooling to room temperature with the furnace.

[0053] The shrinkage rate was calculated using the ceramic core blank size and the ceramic core size measured before and after sintering. The ceramic core prepared in this embodiment was measured and calculated to have a shrinkage rate of 0.42% and a high-temperature deflection of 0.47 mm.

[0054] Example 2

[0055] S1. Prepare 10 kg of ceramic core raw material, weigh quartz glass powder with an average particle size of 20 μm and a purity of 99.96%, zirconium silicate powder with an average particle size of 30 μm and a purity of 99.09%, and metal zirconium powder with an average particle size of 5 μm and a purity of 99.99% in 85%, 12% and 3% by weight respectively; place the quartz glass powder and zirconium silicate powder in a vacuum dryer and dry them for 10 hours at a temperature of 110° C., and fully and evenly mix the dried quartz glass powder and zirconium silicate powder with the metal zirconium powder to obtain a ceramic core raw material;

[0056] Weigh paraffin wax according to 15% of the weight of the ceramic core slurry and put it into a vacuum mixer for melting. Add the evenly mixed ceramic core raw material powder into the melted paraffin wax in batches. The temperature of the paraffin wax is 95°C. Vacuum and stir until uniform to obtain ceramic core slurry.

[0057] S2, transferring the ceramic core slurry to the barrel of the core pressing machine, using a mold to press the green blank, the molding pressure of the core pressing machine is 6MPa, and obtaining the ceramic core green blank;

[0058] S3. Put the ceramic core blank into a sagger, fill it with fillers and then sinter it. According to the first stage, the temperature is from room temperature to 250℃, the heating rate is 2℃ / min, and it is kept at 250℃ for 5h; the second stage is from 250℃ to 450℃, the heating rate is 2℃ / min, and it is kept at 450℃ for 5h; the third stage is from 450℃ to 650℃, the heating rate is 3℃ / min, and it is kept at 650℃ for 8h; the fourth stage is from 650℃ to 950℃, the heating rate is 5℃ / min, and it is kept at 950℃ for 10h; finally, the temperature is increased from 950℃ to 1250℃, the heating rate is 5℃ / min, and it is kept at 12h; finally, the ceramic core is obtained after cooling to room temperature with the furnace.

[0059] The shrinkage rate is calculated using the ceramic core blank size and the ceramic core size measured before and after sintering. The ceramic core prepared in this embodiment is measured and calculated to have a shrinkage rate of 0.03% and a high-temperature deflection of 0.20 mm.

[0060] Example 3

[0061] S1. Prepare 10 kg of ceramic core raw material, weigh quartz glass powder with an average particle size of 20 μm and a purity of 99.97%, zirconium silicate powder with an average particle size of 30 μm and a purity of 99.29%, and metal zirconium powder with an average particle size of 5 μm and a purity of 99.99% in 80%, 15% and 5% by weight respectively; dry the quartz glass powder and zirconium silicate powder in a vacuum dryer for 24 h at a temperature of 95° C., and fully and evenly mix the dried quartz glass powder and zirconium silicate powder with the metal zirconium powder to obtain a ceramic core raw material;

[0062] Weigh paraffin wax according to 12% of the weight of the ceramic core slurry and put it into a vacuum mixer for melting. Add the evenly mixed ceramic core raw material powder into the melted paraffin wax in batches. The temperature of the paraffin wax is 85°C. Vacuum and stir until uniform to obtain ceramic core slurry.

[0063] S2, transferring the ceramic core slurry to the barrel of the core pressing machine, using a mold to press the green blank, the molding pressure of the core pressing machine is 10MPa, and obtaining the ceramic core green blank;

[0064] S3. Put the ceramic core blank into a sagger, fill it with fillers and then sinter it. According to the first stage, the temperature is from room temperature to 150℃, the heating rate is 2℃ / min, and it is kept at 150℃ for 5h; the second stage is from 150℃ to 300℃, the heating rate is 2℃ / min, and it is kept at 300℃ for 5h; the third stage is from 300℃ to 500℃, the heating rate is 3℃ / min, and it is kept at 500℃ for 8h; the fourth stage is from 500℃ to 800℃, the heating rate is 5℃ / min, and it is kept at 800℃ for 10h; finally, the temperature is increased from 800℃ to 1100℃, the heating rate is 5℃ / min, and it is kept at 15h; finally, the ceramic core is obtained after cooling to room temperature with the furnace.

[0065] The shrinkage rate was calculated using the ceramic core blank size and the ceramic core size measured before and after sintering. The ceramic core prepared in this embodiment was measured and calculated to have a shrinkage rate of -0.19% and a high-temperature deflection of 0.50 mm.

[0066] Example 4

[0067] S1. Prepare 10 kg of ceramic core raw material, weigh quartz glass powder with an average particle size of 40 μm and a purity of 99.98%, zirconium silicate powder with an average particle size of 20 μm and a purity of 99.39%, and metal zirconium powder with an average particle size of 5 μm and a purity of 99.99% in accordance with weight percentages of 70%, 20% and 10% respectively; dry the quartz glass powder and zirconium silicate powder in a vacuum dryer for 10 h at a temperature of 1115° C., and fully and evenly mix the dried quartz glass powder and zirconium silicate powder with the metal zirconium powder to obtain a ceramic core raw material;

[0068] Weigh paraffin wax according to 10% of the weight of the ceramic core slurry and put it into a vacuum mixer for melting. Add the evenly mixed ceramic core raw material powder into the melted paraffin wax in batches. The temperature of the paraffin wax is 80°C. Vacuum and stir until uniform to obtain ceramic core slurry.

[0069] S2, transferring the ceramic core slurry to the barrel of the core pressing machine, using a mold to press the green blank, the molding pressure of the core pressing machine is 8MPa, and obtaining the ceramic core green blank;

[0070] S3, put the ceramic core blank into the sagger, fill it with filler and then sinter it, according to the first stage from room temperature to 200℃, the heating rate is 2℃ / min, and keep it at 200℃ for 5h; the second stage is 200℃ to 400℃, the heating rate is 2℃ / min, and keep it at 400℃ for 5h; the third stage is 400℃ to 700℃, the heating rate is 3℃ / min, and keep it at 700℃ for 8h; the fourth stage is 700℃ to 1000℃, the heating rate is 5℃ / min, and keep it at 1000℃ for 8h; finally, increase the temperature from 1000℃ to 1300℃, the heating rate is 5℃ / min, and keep it at 10h; finally, cool it to room temperature with the furnace to obtain the ceramic core.

[0071] The shrinkage rate was calculated using the ceramic core blank size and the ceramic core size measured before and after sintering. The ceramic core prepared in this embodiment was measured and calculated to have a shrinkage rate of -0.05% and a high-temperature deflection of 0.38 mm.

[0072] Example 5

[0073] S1. Prepare 10 kg of ceramic core raw material, weigh quartz glass powder with an average particle size of 50 μm and a purity of 99.99%, zirconium silicate powder with an average particle size of 10 μm and a purity of 99.59%, and metal zirconium powder with an average particle size of 10 μm and a purity of 99.99% in 88%, 10.5% and 1.5% weight percentages respectively; dry the quartz glass powder and zirconium silicate powder in a vacuum dryer for 20 hours at a temperature of 100 ° C, and fully and evenly mix the dried quartz glass powder and zirconium silicate powder with the metal zirconium powder to obtain a ceramic core raw material;

[0074] Weigh paraffin wax according to 18% of the weight of the ceramic core slurry and put it into a vacuum mixer for melting. Add the evenly mixed ceramic core raw material powder into the melted paraffin wax in batches. The temperature of the paraffin wax is 85°C. Vacuum and stir until uniform to obtain ceramic core slurry.

[0075] S2, transferring the slurry to the barrel of a core pressing machine, using a mold to press the blank, the molding pressure of the core pressing machine is 7MPa, and obtaining a ceramic core blank;

[0076] S3. Put the ceramic core blank into a sagger, fill it with fillers and then sinter it. According to the first stage, the temperature is from room temperature to 200°C, the heating rate is 3°C / min, and it is kept at 200°C for 5 hours; the second stage is from 200°C to 400°C, the heating rate is 3°C / min, and it is kept at 400°C for 5 hours; the third stage is from 400°C to 650°C, the heating rate is 5°C / min, and it is kept at 650°C for 8 hours; the fourth stage is from 650°C to 900°C, the heating rate is 5°C / min, and it is kept at 900°C for 10 hours; finally, the temperature is increased from 900°C to a maximum of 1200°C, the heating rate is 8°C / min, and it is kept at 12 hours; finally, the ceramic core is obtained after cooling to room temperature with the furnace.

[0077] The shrinkage rate was calculated using the ceramic core blank size and the ceramic core size measured before and after sintering. The ceramic core prepared in this embodiment was measured and calculated to have a shrinkage rate of 0.02% and a high-temperature deflection of 0.10 mm.

[0078] Example 6

[0079] S1. Prepare 10 kg of ceramic core raw material, weigh quartz glass powder with an average particle size of 30 μm and a purity of ≥99.95%, zirconium silicate powder with an average particle size of 15 μm and a purity of ≥98.99%, and metal zirconium powder with an average particle size of 3 μm and a purity of ≥99.99% according to weight percentages of 87%, 11% and 2% respectively; place the quartz glass powder and zirconium silicate powder in a vacuum dryer and dry them for 15 hours at a temperature of 100 ° C. Fully and evenly mix the dried quartz glass powder and zirconium silicate powder with the metal zirconium powder to obtain a ceramic core raw material;

[0080] Weigh paraffin wax according to 16% of the weight of the ceramic core slurry and put it into a vacuum mixer for melting. Add the evenly mixed ceramic core raw material powder into the melted plasticizer paraffin wax in batches. The temperature of the paraffin wax is 90°C. Vacuum and stir until uniform to obtain ceramic core slurry.

[0081] S2, transferring the slurry to the barrel of a core pressing machine, using a mold to press the blank, the molding pressure of the core pressing machine is 9 MPa, and obtaining a ceramic core blank;

[0082] S3. Put the ceramic core blank into a sagger, fill it with fillers and then sinter it. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 2℃ / min, and it is kept at 200℃ for 4h; the second stage is from 200℃ to 400℃, the heating rate is 2℃ / min, and it is kept at 400℃ for 5h; the third stage is from 400℃ to 650℃, the heating rate is 3℃ / min, and it is kept at 650℃ for 8h; the fourth stage is from 650℃ to 950℃, the heating rate is 5℃ / min, and it is kept at 950℃ for 10h; the fifth stage is from 950℃ to 1250℃, the heating rate is 8℃ / min, and it is kept at 12h; finally, the ceramic core is obtained after cooling to room temperature with the furnace.

[0083] The shrinkage rate was calculated using the ceramic core blank size and the ceramic core size measured before and after sintering. The ceramic core prepared in this embodiment was measured and calculated to have a shrinkage rate of 0.01% and a high-temperature deflection of 0.05 mm.

[0084] Comparative Example 1

[0085] S1. Prepare 10 kg of ceramic core raw material, weigh quartz glass powder with an average particle size of 20 μm and a purity of 99.95%, and zirconium silicate powder with an average particle size of 30 μm and a purity of 98.99% in weight percentages of 90% and 10% respectively, place the quartz glass powder and zirconium silicate powder in a vacuum dryer and dry them for 12 hours at a temperature of 120°C; add the dried and evenly mixed ceramic core raw material powder in batches to the melted paraffin at a temperature of 90°C, evacuate and stir until uniform, and obtain a ceramic core slurry.

[0086] S2. The ceramic core slurry is transferred to the barrel of the core pressing machine, and a green blank is pressed by a mold at a molding pressure of 5 MPa to obtain a ceramic core green blank.

[0087] S3, placing the ceramic core blank into a sagger, filling it with fillers and then sintering it, wherein the final firing temperature is 1250° C., the heat preservation time is 10 hours, and the blank is taken out after cooling to room temperature in the furnace to obtain a ceramic core.

[0088] The shrinkage rate was calculated using the ceramic core blank size and the ceramic core size measured before and after sintering. The ceramic core prepared in this comparative example was measured and calculated to have a shrinkage rate of 1.15% and a high-temperature deflection of 0.71 mm.

[0089] By comparing the above examples with the comparative examples, it is found that the dimensional accuracy of the ceramic cores prepared by the techniques and parameters adopted in Examples 1-6 is higher than that of the comparative examples without the introduction of metal zirconium, indicating that the introduction of metal zirconium can effectively control the dimensional accuracy and stability of the ceramic cores.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0091] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

Claims

1. A raw material for a near-zero shrinkage silicon-based ceramic core, comprising refractory powder and a mineralizer, characterized in that: It also includes metal zirconium powder, the mineralizer is zirconium silicate powder, the weight percentage of the refractory powder in the raw material is 70-89%, the weight percentage of the zirconium silicate powder in the raw material is 10-20%, and the weight percentage of the metal zirconium powder in the raw material is 1-10%.

2. The raw material of the near-zero shrinkage silicon-based ceramic core according to claim 1, characterized in that: The weight percentage of the refractory powder in the raw material is 80-89%, the weight percentage of the zirconium silicate powder in the raw material is 10-15%, and the weight percentage of the metal zirconium powder in the raw material is 1-5%.

3. The raw material of the near-zero shrinkage silicon-based ceramic core according to claim 2, characterized in that: The weight percentage of the refractory powder in the raw material is 85-88%, the weight percentage of the zirconium silicate powder in the raw material is 10.5-12%, and the weight percentage of the metal zirconium powder in the raw material is 1.5-3%.

4. The raw material of the near-zero shrinkage silicon-based ceramic core according to claim 1, characterized in that: The particle size range of the refractory powder is 1-60 μm and the powder purity is not less than 99.95%, the particle size range of the zirconium silicate powder is 1-50 μm and the powder purity is not less than 98.99%, and the particle size range of the metal zirconium powder is 1-10 μm and the powder purity is not less than 99.99%.

5. The raw material of the near-zero shrinkage silicon-based ceramic core according to any one of claims 1 to 4, characterized in that: The refractory material powder is quartz glass powder.

6. A method for preparing a near-zero shrinkage silicon-based ceramic core, using the raw material of the near-zero shrinkage silicon-based ceramic core as described in any one of claims 1 to 5 to prepare a ceramic core, characterized in that: The preparation method specifically comprises: S1, mixing ceramic core raw materials to form ceramic core slurry; S2, forming a ceramic core blank using the ceramic core slurry; S3, burying the ceramic core blank with powder and sintering to obtain a ceramic core.

7. The method for preparing a near-zero shrinkage silicon-based ceramic core according to claim 6, characterized in that: In step S1, the ceramic core raw material is added to the dispersant in batches, and vacuum-stirred until uniform to obtain a ceramic core slurry.

8. The method for preparing a near-zero shrinkage silicon-based ceramic core according to claim 7, characterized in that: In step S1, the ceramic core raw material is added to the melted paraffin in batches, and vacuumed and stirred until uniform to obtain a ceramic core slurry; The melting temperature of the paraffin wax is 80-95°C.

9. The method for preparing a near-zero shrinkage silicon-based ceramic core according to claim 6, characterized in that: In step S2, the ceramic core slurry is added into a core pressing machine, and a ceramic core blank is obtained by a hot pressing injection molding method; The molding pressure of the core pressing machine is 5-10MPa.

10. The method for preparing a near-zero shrinkage silicon-based ceramic core according to claim 6, characterized in that: In step S3, the final sintering temperature is 1100-1300°C, the sintering temperature rise process includes multiple stages, the temperature rise range of each stage is 150-300°C, the temperature rise rate of each stage is 2-8°C / min, and the holding time after each stage of temperature rise is 4-15h; The multiple stages include: the first stage: room temperature to 200°C, the heating rate is 2°C / min, and the temperature is kept at 200°C for 4 hours; the second stage: 200°C to 400°C, the heating rate is 2°C / min, and the temperature is kept at 400°C for 5 hours; the third stage: 400°C to 650°C, the heating rate is 3°C / min, and the temperature is kept at 650°C for 8 hours; the fourth stage: 650°C to 950°C, the heating rate is 5°C / min, and the temperature is kept at 950°C for 10 hours; the fifth stage: 950°C to a maximum of 1250°C, the heating rate is 8°C / min, and the temperature is kept for 12 hours.

Citation Information

Patent Citations

  • Titanium casting investment material for oral cavity and application method thereof

    CN101849888A

  • Preparation method of embedding material for pure-titanium baked porcelain substrate

    CN104523441A

  • Silica-based ceramic mold core and preparation method thereof

    CN106747369A

  • Silicon-based ceramic core material, preparation method and silicon-based ceramic core

    CN114907133A

  • Raw materials of low-shrinkage low-deflection silicon-based ceramic core and preparation method of low-shrinkage low-deflection silicon-based ceramic core

    CN115108818A

Cited By

  • Preparation method and application of 3D printing silicon-based ceramic core

    CN117534451A

  • A preparation method and application of a 3D printed silicon-based ceramic core

    CN117534451B

  • Siliceous furnace lining material for smelting environment with high scrap ratio and preparation method of siliceous furnace lining material

    CN121405486A

  • Preparation method of high-entropy rare earth silicate coated particle reinforced silicon-based ceramic core

    CN121735629A

  • Preparation method of aluminum-based ceramic core

    CN122254871A